Decreasing Complications in Distal Hypospadias Surgery, with Single Stage Repairs - Asif Aziz, Mansoor Khan, Hidayat Ullah, Obaidullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hypospadias is one of the most common congenital anomalies of male population. The diversity of presentation, and the evolution of its surgical management have rendered the acceptance of a standard protocol. This article reports on the outcomes and complications of single stage tubularization for distal and midshaft hypospadias with no or mild ventral curvature. Material and Methods: A total of 128 patients, with age range of 8 months to 28 years were included. All had distal or midshaft hypospadias with no or mild ventral curvature, with no previous procedures. All patients undergone two types of surgical repairs, Glanular Approximation Procedure and Tubularized Incised Plate urethoplasty. Results: Most patients had smooth postoperative recovery. All patients were followed for six months to one year. Major complication of concern were urethra-cutaneous fistula in 8 (6%) and glanular dehiscence in 2 (2%) of patients, which required surgical closure. Practical Implications: The practical implications of hypospadias surgery include improved urinary function, reduced risk of infections, improved sexual function, and improved psychological well-being. Keywords: Hypospadias, Tubularization, Urethroplasty, Glanular approximation procedure, Incised Plate Urethroplasty